The Effect Of Intellectual Intelligence And Soft Skill On Agent Recruitment Pt. Sequis Life Branch Mmtc Medan - Michael Tek Kaslim Putra; Thomas Sumarsan Goh; Wily Julitawaty; Syawaluddin (Enrichment : Journal of Management, 2022)
Intellectual Intelligence is able to work to measure speed, measure new things, store and recall objective information and play an active role in calculating numbers and others. Soft Skills are abilities beyond technical and academic abilities, which prioritize intrapersonal and interpersonal skills. Recruitment is a process that begins with a desire to fill available job vacancies until the applicant submits his application file. This study uses multiple linear regression analysis method to determine the relationship of each independent variable to the dependent variable. Samples were taken using a saturated sampling technique where all members of the population were used as samples. The research scale used is a Likert scale. The results of the partial hypothesis test show that partially, each variable of intellectual intelligence and soft skills has a significant effect on work conflict at PT. Sequis Life Medan. Simultaneous hypothesis test results show that simultaneously, soft skills have a significant effect on agent recruitment at PT. Sequis Life Medan